Lactoferrin Solution as a New Natural Photosensitizer in Photodynamic Therapy Against Oral Candida spp. Multidrug-Resistant Isolates: A Preliminary In Vitro Study - Cinzia Casu; Andrea Butera; Alice Piga; Andrea Scribante; Sara Fais; Germano Orrù (Microorganisms, 2025)
Serious oral infections are frequently caused by Candida species, which have lately demonstrated resistance to antifungal medications. As a result, new therapeutic strategies, like photodynamic therapy (PDT), are desperately needed. Lactoferrin (LF), a salivary enzyme, is a natural protein that binds iron and has antifungal properties. Given its chemical structure and light absorption at 310–350 nm, LF appears to be a good photosensitizer in a PDT process for treating oral candidiasis. The purpose of this work was to assess the effectiveness of lactoferrin (LF) as a photosensitizer (PS) in photodynamic treatment (PDT) against oral multidrug-resistant (MDR) isolates of Candida spp. using an in vitro investigation. For this in vitro investigation, oral MDR isolates of Candida albicans, Candida kruseii, and Candida glabrata were employed. Using a Kirby–Bauer test (Eucast protocol), a solution of 20 mg of bovine lactoferrin dissolved in 1 mL of Sabouraud’s broth was tested in four different experimental combinations: (i) the solution as it is; (ii) the solution activated with 3% H2O2; (iii) the solution activated by light at 310–350 nm; and (iv) the solution activated with both 3% H2O2 and light at 310–350 nm. A control group and one with only H2O2 were also tested. After that, the Petri plates were incubated for 48 h at 37 °C. With inhibitory halos ranging from 30 to 40 mm for all Candida spp. MDR analyzed, group (iv) displayed the greatest results. H2O2 + lactoferrin-based solutions are thought to be potential PS in PDT for MDR Candida spp. eradication.